E-Commerce, Financial Technology, Media Sosial, Modal Usaha, Dan Pendapatan Usaha Mikro, Kecil, Dan Menengah Di Bidang Fashion - Wahdia, Mila; Rintasari, Nugraheni (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2023)
This study aims to analyze the impact of e-commerce, fintech, social media and entrepreneurial capital in increasing the income of fashion MSMEs in the Sleman Regency area. This research is a quantitative research. The sample of this study amounted to 85 respondents. Select samples according to reasonable sampling methods. The data analysis technique used to answer the hypothesis is multiple regression with F test and t test. The results of this study show that e-commerce, fintech, and social media have no effect on revenue growth, while venture capital simultaneously has a positive effect on revenue growth. An R-squared value of 0.572 indicates that the explanatory power of the independent variable to the dependent variable is 57.2%.